2017
DOI: 10.1186/s12967-017-1361-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and histological effects of MR-guided pulsed focused ultrasound to the rat heart

Abstract: BackgroundImage-guided high intensity focused ultrasound has been used as an extracorporeal cardiac pacing tool and to enhance homing of stem cells to targeted tissues. However, molecular changes in the myocardium after sonication have not been widely investigated. Magnetic-resonance (MR)-guided pulsed focused ultrasound (pFUS) was targeted to the rat myocardium over a range of pressures and the microenvironmental and histological effects were evaluated over time.MethodsEight-to-ten-week-old Sprague–Dawley rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 70 publications
4
12
1
Order By: Relevance
“…Under MR guidance, the left ventricle was sonicated with 3 MPa of PNP, which is approximately 1.6 MPa intramyocardially (equivalent to a MI = 1.7) as a result of attenuation at rat chest wall. 22 Following pFUS treatment, no macroscopic and microscopic evidence of pulmonary damage was observed as has been previously reported at sonications at PNP = 6 MPa. 22…”
Section: Statistical Analysessupporting
confidence: 57%
“…Under MR guidance, the left ventricle was sonicated with 3 MPa of PNP, which is approximately 1.6 MPa intramyocardially (equivalent to a MI = 1.7) as a result of attenuation at rat chest wall. 22 Following pFUS treatment, no macroscopic and microscopic evidence of pulmonary damage was observed as has been previously reported at sonications at PNP = 6 MPa. 22…”
Section: Statistical Analysessupporting
confidence: 57%
“…In those studies tumor-infiltrating lymphocytes were not examined, but the increase in the number of activated, tumor antigen-specific dendritic cells in the draining lymph nodes was observed within 1–3 days following ablation. Similarly, in a study of molecular changes in healthy rat cardiac tissue following milder mechanical disruption by pulsed FUS (Jang et al 2017), infiltrating macrophages and neutrophils were observed within the myocardium 24 hours post treatment, but were undetectable by 48 hours.…”
Section: Discussionmentioning
confidence: 92%
“…The homing process for MSCs is well-characterized: in order to travel from circulation into a target tissue, they must undergo (1) tethering by selectins, (2) activation by chemokines, (3) arrest by integrins, (4) transmigration or diapedesis across the endothelial layer, and (5) extravascular migration to the target tissue mediated by cytokines [49]. pFUS at certain parameters can enhance this process by upregulating homing molecules at the target tissue, especially chemokines like SDF-1 and cell adhesion molecules like VCAM-1 [31][32][33][34]. Many studies have demonstrated increased MSC homing following pFUS [30,32,34,35], but whether the same effect would be true of EVs was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that pFUS can enhance MSC therapy for AKI [ 29 , 30 ], but different mechanisms have been proposed for this effect. The homing hypothesis posits that sound waves transiently upregulate local inflammatory and chemoattractive signals [ 31 33 ]. This local gradient of cytokines, chemokines, and trophic factors has been shown to promote the homing of MSCs to various tissues including the skeletal muscle [ 34 , 35 ] and the kidney [ 29 , 30 , 32 , 36 ].…”
Section: Introductionmentioning
confidence: 99%